Environmental management accounting system adoption and sustainability performance: triple bottom line approach / Nirman Noor Afiqi Mat Yusoh, Tuan Zainun Tuan Mat, and Azizah Abdullah - Mat Yusoh, Nirman Noor Afiqi; Tuan Mat, Tuan Zainun; Abdullah, Azizah (UiTM Press, 2023)
Sustainability development is an ongoing issue facing corporations. With the rapid development of industry, environmental pollution is becoming more prominent globally. Therefore, environmental accountability has become a crucial aspect of corporate social responsibility in the effort to mitigate harm to the environment. The evolving global economy has pressured Malaysian companies to improve their sustainability performance and be accountable towards the environment and society. The Environmental Management Accounting System (EMAS) can enhance sustainability by evaluating financial and physical environment-related information. This research examined the level of EMAS adoption based on the social issue life cycle theory and its impact on sustainability performance, based on a triple bottom line approach. A total of 205 questionnaires were collected from public listed companies (PLCs) in Malaysia. Data were analysed through partial least squares structural equation modelling. The finding indicated EMAS adoption in Malaysia are in the learning phases reflecting that the extent of adoption is moderate. Specifically, this research found that EMAS adoption significantly impacted the economic, environmental and social performance. This research is noteworthy to companies, policymakers and environmental regulatory bodies in understanding the level of EMAS adoption in Malaysia. The research concluded that EMAS is essential in promoting the dimensions of sustainable competitive advantage within organizations.